Tara gum–bovine sodium caseinate acid gels: Stabilisation of W/W emulsions. (13th February 2020) - Hidalgo, Ma. Eugenia; Ingrassia, Romina; Nielsen, Nadia Sol; Porfiri, Ma. Cecilia; Tapia‐Maruri, Daniel; Risso, Patricia Hilda
Abstract : Microstructural, rheological, and textural behaviour of tara gum–bovine sodium caseinate aqueous mixtures and their acid gels were evaluated. Acid gels with different microstructures and texture were obtained. These results can be related to a competition between the protein acid gelation process and the segregative phase separation. Depending on the concentration ratio of both biopolymers, a continuous protein gel network or a water‐in‐water emulsion stabilised by acid gelation was observed. These findings may be used to address the development of new food‐grade gels with different textures and also for the obtention of protein microgels to encapsulate hydrophilic compounds.